Enhancing Resistive Switching in AlN-Based Memristors Through Oxidative Al2O3 Layer Formation: A Study on Preparation Techniques and Performance Impact - Hongxuan Guo; Jiahao Yao; Siyuan Chen; Chong Qian; Xiangyu Pan; Kuibo Yin; Hao Zhu; Xu Gao; Suidong Wang; Litao Sun (Micromachines, 2024)
Aluminum nitride (AlN) with a wide band gap (approximately 6.2 eV) has attractive characteristics, including high thermal conductivity, a high dielectric constant, and good insulating properties, which are suitable for the field of resistive random access memory. AlN thin films were deposited on ITO substrate using the radio-frequency magnetron sputtering technique. Al’s and Au’s top electrodes were deposited on AlN thin films to make a Au/Al/AlN/ITO sandwich structure memristor. The effects of the Al2O3 film on the on/off window and voltage characteristics of the device were investigated. The deposition time and nitrogen content in the sputtering atmosphere were changed to adjust the thickness and composition of AlN films, respectively. The possible mechanism of resistive switching was examined via analyses of the electrical resistive switching characteristics, forming voltage, and switching ratio.